A belt-integrated piezoelectric energy harvester for wearable electronic devices. Issue 1 (10th December 2021) - Beyaz, Mustafa İlker; Ahmed, Naveed
Abstract: This paper reports a novel piezoelectric energy harvester incorporated on a waistbelt for power generation from waist movements. The device is composed of multiple piezoelectric disks in 3 D-printed encapsulations and rectifying circuity, which are connected to a battery for energy storage. The harvester was simulated and tested through different body activities. Measured open circuit voltages up to 19 V, μW-level AC power generation, and energy storage test results clearly demonstrate that the energy harvester presented here can effectively convert waist movements into electrical power, store energy in a battery, and support the batteries of wearable electronic devices for extended operations.